GAP161 targets and downregulates G3BP to suppress cell growth and potentiate cisplaitin‐mediated cytotoxicity to colon carcinoma HCT116 cells - Hao Zhang; Shenghua Zhang; Hongwei He; Wuli Zhao; Jianhua Chen; Rong‐Guang Shao (2012)
Ras-GTPase-activating protein SH3 domain-binding proteins (G3BP) are overexpressed in various human tumors and participate in several signaling pathways involved in growth, differentiation and apoptosis. G3BP interact with RasGAP (Ras-GTPase activating protein) only in growing cells and depend on Ras activation, and participate in the Ras signal pathway. Therefore, the blockage and downregulation of G3BP may be a new strategy for cancer therapy. In this report, we demonstrate that a novel peptide GAP161 blocked the functions of G3BP and markedly suppressed HCT116 cell growth through the induction of apoptosis. The peptide bound with G3BP, which interfered with the interaction of G3BP1 with RasGAP and further suppressed Ras signaling pathways. GAP161 downregulated G3BP1 and G3BP2 proteins. Similarly, the knockdown of G3BP substantially decreased the proliferation of HCT116 cells and inhibited Ras signal pathways. Furthermore, the downregulation of G3BP could enhance cisplatin-induced apoptosis and growth inhibition of HCT116 cells. We also found that GAP161 suppressed the growth of BALB/c mice bearing colon CT26 tumors and nude mice bearing HCT116 xenografts. These results suggest that downregulation of G3BP might be useful in cancer therapy and that GAP161 is a promising new therapeutic agent for cancers.